CHARACTERISTICS OF JOURNALISTIC ACTIVITY IN EMERGENCIES AND SITUATIONS - Ortiqboyeva Mubina Navruzbekovna (American Journals, 2024)
An emergency situation is a situation that can lead to the death of people, damage to people's health or the environment, great material damage to people's life and its disruption in a certain area. it is a situation caused by an accident, disaster, natural disaster, epidemics, epizootics.
Keywords: Emergency situation, state of emergency, area, disaster, disaster, natural disasters: landslide, flood, strong wind, fire, drought, landslide, avalanche, rain work, technogen